A política nacional de resíduos sólidos e o plano diretor municipal de Rio Claro/SP: o uso como instrumento para a gestão urbano-ambiental municipal - Tedrus, Caio Augusto Begossi [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Due to the large economic development associated with the growing consumerist lifestyle of our capitalist society, the problem of uncontrolled solid waste generation worsens, which one is considered to be one of the main responsible factors for environmental degradation. As a case study and in order to solve the problem of large generation of municipal solid waste, this work aims to study the “plano diretor” of Rio Claro city, São Paulo. The “plano diretor” is a municipal law that provides guidelines for the administration of the city, which include guidelines for the management of solid waste generated in the city. The guidelines required in order to write the “plano diretor” are provided by the national law “estatuto da cidade”, providing information for the planning and development of the cities, as well as the management of the urban environment. However, only the “estatuto da cidade” does not provide enough instructions for creating management plans in order to solve the many problems from the urban environment. Thus, studies have been done about urban and environmental management, to understand how municipal management plans should be structured. As a form of seeking information that can complement the “plano diretor” to the creation of policies for managing solid waste of the city, the “Política Nacional de Resíduos Sólidos”(PNRS) emerges in 2010 as a document which provides principles, objectives and guidelines to create plans for Solid Waste Management at the national, state, regional and municipal levels. Therefore, it was possible to make a joint analysis of the “plano diretor” of Rio Claro with the PNRS to identify what is already done within the municipality about the solid waste management, and identify which aspects are most significant in the municipal solid waste management that the national policy provides. Yet studies have been done on the current municipal solid waste management...

Devido ao grande desenvolvimento econômico, associado ao estilo de vida consumista que se vem crescendo em nossa atual sociedade capitalista, agrava-se o problema da geração descontrolada de resíduos sólidos, um dos principais fatores responsáveis pela degradação do meio ambiente. Como forma de solucionar o problema da grande geração de resíduos sólidos urbanos, este trabalho visa o estudo do Plano Diretor Municipal da cidade de Rio Claro-SP como estudo de caso. O Plano Diretor é a lei municipal que dá diretrizes para a administração de todo o município, dentre as quais, diretrizes para a administração de resíduos sólidos gerados no município. A criação do Plano Diretor se dá pelas diretrizes fornecidas pela Lei nacional do Estatuto da Cidade, fornecendo informações para o planejamento e desenvolvimento das cidades, assim como o gerenciamento do meio urbano. Porém, somente o Estatuto da Cidade não fornece instruções o suficiente para a criação de planos de gestão dos diversos problemas no meio urbano. Então, foram feitos estudos nas áreas de gestão e planejamento urbano-ambiental, para se entender como deve ser estruturado e embasado os planos de gestão municipal. Como forma de buscar informações que possam complementar o Plano Diretor na criação de políticas de gestão de resíduos sólidos dentro de um município, surge em 2010 a Política Nacional de Resíduos sólidos (PNRS), documento o qual fornece princípios, objetivos e diretrizes para a elaboração de Planos de Gestão de Resíduos Sólidos, a nível nacional, estadual, regional e municipal. Desta forma, foi possível fazer a análise em conjunto do Plano Diretor Municipal de Rio Claro com a PNRS para identificar o que se já é feito dentro do município a respeito da gestão de resíduos sólidos, assim como identificar quais são os aspectos mais significativos dentro da gestão municipal de resíduos sólidos que a política nacional pode...
Keywords: Política Nacional de Resíduos Sólidos (Brasil); Resíduos; Planejamento municipal; Resíduos sólidos; Planejamento urbano; Gestão ambiental - Rio Claro (SP)